Novas espécies de Yungasia Linnavuori (Hemiptera, Cicadellidae, Deltocephalinae) - Zanol, K. M. R. (Acta Biológica Paranaense, 2012)
<htm>Novas espécies de Yungasia Linnavuori (Hemiptera, Cicadellidae, Deltocephalinae) </htm>